MEMPROGRAMKAN AKSES PEMBIAYAAN SYARIAH BAGI USAHA MIKRO KECIL DAN MENENGAH DI DESA CIARUTEUN ILIR, KECAMATAN CIBUNGBULANG, KABUPATEN BOGOR - Rully Trihantana; Ermi Suryani; Eri Ariyanto (SAHID DEVELOPMENT JOURNAL, 2022)
This community service aims to program access to sharia financing for Micro, Small and Medium Enterprises. The subject of this community service is the people of Ciaruteun Ilir Village, Cibungbulang District, Bogor Regency, West Java Province. In this community service, activities are carried out that can provide enlightenment to MSMEs. Islamic banks and Islamic microfinance institutions must assist MSMEs in running their business so that sharia financing provided to MSMEs can be in line with the objectives of sharia financing. In addition, Islamic banks and Islamic microfinance institutions need to be intensely involved in monitoring and ensuring that MSMEs that receive financing assistance are able to manage their finances properly. With this community service, it can be concluded that people who are involved in MSMEs need to continue to increase their understanding that sharia financing will increase their income and welfare and of course it will directly reduce poverty. In addition, the presence of the MSME community is expected to become an extension in introducing and educating ordinary people (non-SMEs) to be involved in business activities that involve Islamic banks and Islamic financial institutions.